The Effect of Advertising and Consumer Satisfaction on Consumer Loyalty to Pepsodent Products in Banda Aceh City - Zulfan Yusuf; Sarboini Sarboini; Mariati Mariati; Saiful Amri; Syamsul Rizal (International Journal of Management Science and Information Technology, 2021)
This study aims to determine the effect of advertising and consumer satisfaction on consumer loyalty to Pepsodent products in Banda Aceh City. The population in this study were Pepsodent consumers in Banda Aceh City, with a total sample of 100 respondents using convenience sampling technique. The model used in this study is multiple linear regression analysis. The results showed that advertising and consumer satisfaction had a significant effect on consumer loyalty to Pepsodent products in Banda Aceh City by 80.2% and the remaining 19.8% was explained by other variables outside of this study such as product quality, brand image and price and etc. The value of the correlation coefficient (R) indicates that the relationship (correlation) between the independent variable and the dependent variable is 89.6%, meaning that consumer loyalty to Pepsodent products in Banda Aceh City has a strong and positive relationship with correlation advertisement(X1) and consumer satisfaction (X2). The results of the f test statistic test show that advertising and consumer satisfaction simultaneously have a significant effect on consumer loyalty to Pepsodent products in Banda Aceh City, with value Fcount>Ftable (197,035>3,090).While partially advertising and customer satisfaction have a significant effect on consumer loyalty to Pepsodent products in Banda Aceh City, with a value of tcount> ttable (9.705 and 3.339>1.984). Based on the results of multiple linear regression analysis, it can be seen that from the two variables studied, it turns out that the variable advertisement(X1) has the most dominant influence on consumer loyalty to Pepsodent products in Banda Aceh City, with a coefficient value of 0.689, and then followed by the variable consumer satisfaction(X2) with a coefficient value of 0.264.